O plano de desenvolvimento da escola (PDEE) como expressão do gerencialismo na educação - Speck, Raquel Angela (2012)
This study has as objective to contribute to the understanding of managemental administration model, applied to the field of educational management. For that, it searched to evidence the main points that characterize this type of management, identifying, initially, the ways in which it reveals itself in public administration and the possible implications for educational management. The research elected as analysis object the Plan of Development of the School (PDEE), a program of the Ministry of Education - MEC for school management. By the analysis of its theoretical methodological beddings, it sought to identify to what extent the program makes use of the managerialist conception in and for education management. First of all, the study oriented itself towards the understanding of the reform of Administrative Apparatus of the State, whereas the international context of administrative reforms and capitalist restructuring. After that, it analyzed the way that education reform was conducted and the educational politics resulting of it. The accomplished study evidenced the bases of sustentation of PDEE, its entailing with the FUNDESCOLA and also with the Education Development Plan (PDE). The proposed analysis aimed to show in what dimension Brazilian education reform incorporated and materialized the most important aspects of the managerial proposal of State reform, underlying to the organization, financing and management, instituting a framework of directed politics to attribute greater responsibility to local spheres (city departments of education and pertaining to school units). Understanding the PDEE as a result of this context of reforms, this research demonstrates despite the program in analysis emphasizes technician and organizational aspects of school management, with sights to endow it with bigger ―efficiency‖, in detriment of that relative to education and learning. In conclusive terms, the research points that the PDEE, while proposal, presents elements that characterize the managemental model of administration, originating from practices of private sector.